Global Health Determinants Perceived and Expressed by Children and Adolescents Between 6 and 17 Years: A Systematic Review of Qualitative Studies - Deyra, Maéliane; Gay, Chloé; Gerbaud, Laurent; Berland, Pauline; Pizon, Frank (Frontiers in Pediatrics, 2020)
Aim: To identify the determinants of global health in the literature as perceived and expressed by children and adolescents in order to adapt prevention actions to this young audience. To also question the pertinence of a qualitative approach when interviewing children. Method: Systematic review of the literature from PubMed, Google Scholar, CINAHL, PsycINFO databases. The studies selected used qualitative methods alone for investigating the views of health determinants in children and adolescents. Results: 185 articles were read to reach a final selection of 13 articles on global health, excluding studies with children who were ill, studies using quantitative, mixed, or retrospective methodologies, and those dealing exclusively with themes of health. Collecting information from children and adolescents showed the pertinence and effectiveness of qualitative methods. It also appears necessary to explore new paths: improving and adapting the tools and methodological supports used and combining them to enrich repositories. Conclusion: The small amount of qualitative data available with the views of children and adolescents on health determinants requires that new studies with better adapted collection methodologies be set up. To increase pertinence and effectiveness among a young audience, it is necessary, considering the methodologies identified during this literature review, to turn towards a multi-phase method that combines these methods. A methodology in several phases allows each one to use a different approach with young people and to obtain richer and more varied information. A corpus of images appeared as a powerful tool for collection: it facilitates children’s capacity for oral expression and places the researcher in a position of listening.